Ethical Considerations in Medical Treatment to Jehova Witnesses - Cardemil H., Gonzalo (Acta Bioethica, 2010)
Currently, it would be unthinkable to treat a patient without explaining him his complications and possible morbidity,without mentioning alternative treatments or, worst, oblige or deceive him giving treatment that he rejects.The case of Jehova Witnesses is worth considering. National and international experience show solid scientific base for thepracticability of complex surgeries without the use of blood, some of them unthinkable years before.The present article refers to some legal-ethical norms, Chilean as well as International, referring to the autonomy and nondiscriminating patients, and it shows the experience of the University of Chile Hospital Clinic that, since 1988, counts witha successful health care program for patients who do not wish blood transfusions.